Novel LCAT (Lecithin: Cholesterol Acyltransferase) Activator DS-8190a Prevents the Progression of Plaque Accumulation in Atherosclerosis Models. Issue 1 (January 2021) - Sasaki, Masato; Delawary, Mina; Sakurai, Hidetaka; Kobayashi, Hideki; Nakao, Naoki; Tsuru, Hiromi; Fukushima, Yumiko; Honzumi, Shoko; Moriyama, Sachiko; Wada, Naoya; Kaneko, Toshio; Yamada, Keisuke; et al.
Abstract : Objective: Enhancement of LCAT (lecithin:cholesterol acyltransferase) activity has possibility to be beneficial for atherosclerosis. To evaluate this concept, we characterized our novel, orally administered, small-molecule LCAT activator DS-8190a, which was created from high-throughput screening and subsequent derivatization. We also focused on its mechanism of LCAT activation and the therapeutic activity with improvement of HDL (high-density lipoprotein) functionality. Approach and Results: DS-8190a activated human and cynomolgus monkey but not mouse LCAT enzymes in vitro. DS-8190a was orally administered to cynomolgus monkeys and dose dependently increased LCAT activity (2.0-fold in 3 mg/kg group on day 7), resulting in HDL cholesterol elevation without drastic changes of non-HDL cholesterol. Atheroprotective effects were then evaluated using Ldl-r KO × hLcat Tg mice fed a Western diet for 8 weeks. DS-8190a treatment achieved significant reduction of atherosclerotic lesion area (48.3% reduction in 10 mg/kg treatment group). Furthermore, we conducted reverse cholesterol transport study using Ldl-r KO × hLcat Tg mice intraperitoneally injected with J774A.1 cells loaded with [ 3 H]-cholesterol and confirmed significant increases of [ 3 H] count in plasma (1.4-fold) and feces (1.4-fold on day 2 and 1.5-fold on day3) in the DS-8190a–treated group. With regard to the molecular mechanism involved, direct binding of DS-8190a to human LCAT protein was confirmed by 2 different approaches: affinity purification by DS-8190a–immobilized beads and thermal shift assay. In addition, the candidate binding site of DS-8190a in human LCAT protein was identified by photoaffinity labeling. Conclusions: This study demonstrates the potential of DS-8190a as a novel therapeutic for atherosclerosis. In addition, this compound proves that a small-molecule direct LCAT activator can achieve HDL-C elevation in monkey and reduction of atherosclerotic lesion area with enhanced HDL function in rodent. Abstract : Supplemental Digital Content is available in the text.